2015
DOI: 10.1371/journal.pone.0141038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Critical Amino Acids Conferring Lethality in VopK, a Type III Effector Protein of Vibrio cholerae: Lessons from Yeast Model System

Abstract: VopK, a type III effector protein, has been implicated in the pathogenesis of Vibrio cholerae strains belonging to diverse serogroups. Ectopic expression of this protein exhibits strong toxicity in yeast model system. In order to map critical residues in VopK, we scanned the primary sequence guided by available data on various toxins and effector proteins. Our in silico analysis of VopK indicated the presence of predicted MCF1-SHE (SHxxxE) serine peptidase domain at the C-terminus region of the protein. Substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Previously, yeast has been used as a model organism to study the activity of several other V. cholerae T3SS effector proteins (Tripathi et al, 2010, 2013; Bankapalli et al, 2015; Seward et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, yeast has been used as a model organism to study the activity of several other V. cholerae T3SS effector proteins (Tripathi et al, 2010, 2013; Bankapalli et al, 2015; Seward et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Yeast growth assays were performed as described earlier (Tripathi et al, 2010 ; Bankapalli et al, 2015 ). Briefly, overnight cultures of all recombinant strains in selective SC Raf medium were diluted and grown again in same media at 30°C until exponential phase (OD 600 ~ 0.8–1.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In AM-19226, no 3' encoded effector is required for infant mouse colonization, but in an infant rabbit model of infection, moderate reductions in the incidence and severity of diarrhea as well as a slight decrease in colonization is observed during infection with VopK or VopY deletion strains [18]. In yeast, VopK toxicity is dependent on residues in the C-terminal domain postulated to comprise an MCF1-SHE serine peptidase domain, although peptidase activity was not detected and motif conservation is imprecise [80].…”
Section: Core Encoded Effectorsmentioning
confidence: 99%
“…Previous studies using O39 serogroup strain AM-19226, which lacks the TCP and CT, have shown that T3SS activity is required for colonization and disease in murine and rabbit animal models of infection (24,25). T3SS genomic island-encoded, translocated proteins have been identified and named Vops, and several Vops have been assigned functions (25)(26)(27)(28)(29)(30).…”
Section: Importancementioning
confidence: 99%